Teething Beliefs, Misconceptions, and Practices Among Mothers Attending a Tertiary Hospital in Nigeria: Implications for Child Health and Clinical Practice - Olatunya, Oladele Simeon; Adeniyi, Adewuyi Temidayo; Babatola, Adefunke Olarinre; Fatunla, Odunayo Tolulope; Olajuyin, Oyebanji Anthony; Ogundare, Ezra Olatunde; Komolafe, Akinwumi Kolawole; Fadare, Joseph Olusesan; Oyelami, Oyeku Akibu (Journal of Nepal Paediatric Society, 2020)
Introduction: Teething is a physiologic process that begins during infancy. However, some mothers often attribute certain symptoms to teething. In this study, we assessed the opinions and practices of mothers attending a tertiary health facility in Nigeria on teething. Methods: This was a cross-sectional, descriptive study conducted among caregivers of children presenting to the out-patient department of a tertiary hospital, Southwestern Nigeria. Results: Five hundred and sixteen mothers were studied. The leading symptoms attributed to teething were fever 420 (81.4%), reduced food intake / appetite 320 (62.0%), diarrhoea 314 (60.9%) and vomiting 294 (57.0%). Some believed that teething is associated with convulsion 102 (19.8%), mouth ulcers 69 (13.4%), ear discharge 68 (13.2%), and no symptoms 41 (7.9%). Majority of the mothers 374 (72.5%) believed that teething requires treatment. Two hundred and four (39.5%) mothers had given their children oral analgesics for teething while 194 (37.6%) administered teething mixtures. These medications were more likely to be prescribed at the hospital or purchased over the counter (p < 0.05). Other treatments given included herbal concoction 46 (8.9%), local tooth extraction 22 (4.3%), enema 17 (3.3%), body scarifications 14 (2.7%), gum fomentation 14 (2.7%) and gum incision 12 (2.3%). Responders who attributed convulsion to teething were more likely to have incised their children’s gums (p < 0.05). Conclusions: This study revealed that sundry symptoms were attributed to teething and harmful home interventions were done for teething. There is a need to educate the society on teething and discourage harmful practices for teething by caregivers.